2020
DOI: 10.1002/suco.201900283
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of the corrosion effects in prestressed concrete beams without shear reinforcement

Abstract: Corrosion of prestressed concrete structures causes size reduction of strands, degradation of mechanical properties of steel, cracking of the surrounding concrete, and bond decay at steel-to-concrete interface. In this paper, a numerical approach able to take into account all the effects involved in the corrosion process by using nonlinear finite element analysis (NLFEA) and membrane or shell elements modeling is proposed. Two different strategies are adopted to model strands: the smeared and the discrete appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
(77 reference statements)
0
30
0
Order By: Relevance
“…For the reinforcement, one‐dimensional fully embedded reinforcement was applied for which perfect bond between the reinforcement and the neighboring concrete elements was assumed. This assumption can be justified by the work of Belletti et al, 21 who found that a model without a bond‐slip relation is able to give a good approximation of the load–displacement curve and the localization of failure. Nonlinear material properties were assigned to these reinforcement elements.…”
Section: Finite Element Modelingmentioning
confidence: 97%
“…For the reinforcement, one‐dimensional fully embedded reinforcement was applied for which perfect bond between the reinforcement and the neighboring concrete elements was assumed. This assumption can be justified by the work of Belletti et al, 21 who found that a model without a bond‐slip relation is able to give a good approximation of the load–displacement curve and the localization of failure. Nonlinear material properties were assigned to these reinforcement elements.…”
Section: Finite Element Modelingmentioning
confidence: 97%
“…PARC_CL 2.1 can be applied for the prediction of the cyclic and dynamic response of RC structures since it includes the effects of plastic and irreversible deformations in the unloading-reloading phase [20]. The model also allows to correctly catch other aspects which can be very important in the analysis of existing RC structures, such as the buckling of longitudinal reinforcement [21], time-dependent effects and the corrosion of reinforcement [22], which however lie outside of the scope of this work.…”
Section: Modelling Assumptionsmentioning
confidence: 99%
“…Corrosion of prestressed reinforced concrete structures leads to a decrease in the size of reinforcement, deterioration of mechanical properties of steel, cracking of surrounding concrete, and decay of bonds at the interface «steel-concrete». Paper [32] proposes a numerical approach that can take into consideration all the effects associated with the corrosion process using a nonlinear analysis of the finite elements (NLFEA) and modeling of membrane or shell elements. The cited work is based on a huge theoretical base and computer simulation; however, it would be good to support it with experimental research.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%